Translational treatment of aphasia combining neuromodulation and behavioral intervention for lexical retrieval: implications from a single case study - Galletta, Elizabeth E.; Vogel-Eyny, Amy (Frontiers in Human Neuroscience, 2015)
Background Transcranial direct current stimulation (tDCS), a non-invasive method of brain stimulation, is an adjunctive research-therapy for aphasia. The concept supporting translational application of tDCS is that brain plasticity, facilitated by language intervention, can be enhanced by non-invasive brain stimulation. This study combined tDCS with an ecologically-focused behavioral approach that involved training nouns and verbs in sentences. Method Participant: A 43-year-old, right-handed male with fluent-anomic aphasia who sustained a single-left-hemisphere-temporal-parietal stroke was recruited. Treatment: Instrumentation included the Soterix Medical 1x1 Device. Anodal tDCS was applied over Broca’s area. Behavioral materials included: sentence production, naming in the sentence context, and implementation of a social-conversational-discourse treatment. Design and Procedures: The independent variable of this crossover case-study was tDCS, and the dependent variables were language and quality-of-life measures. In each session the subject received language treatment with the first twenty minutes additionally including tDCS. Results Performance in naming nouns and verbs in single words and sentences were obtained. Verb production in the sentence context increased after active anodal tDCS and speech-language treatment. Conclusion Aphasia treatment that involves naming in the sentence context in conjunction with translational application of tDCS may be a promising approach for language-recovery post stroke.